Concentration of Media or Concentration of Topics In Peruvian Digital Journalism. A Quantitative Approach to the Problem - Sánchez Flores, Miguel (2019)
This article presents some of the main findings of the research project “Concentration of media or concentration of topics in Peruvian journalism? An analysis of the contents of the 3 news websites in Peru (El Comercio, La República and Radio Programas del Perú), whose objective was to analyze the work of producing their own content in three of the most important digital newsrooms of the country and, with it, verify the variety of information that exists inside the Peruvian digital journalism market. Likewise, the text presents the proposed methodology and analyzes the results of the research, making special emphasis on two of the four study categories: “sections” and “sources of origin”. The investigation reveals if in Peru, we not only attend a media concentration in the printed sector, where the El Comercio Group handles close to 80% of the national circulation market, but also exists a concentration of topics in which the main digital media “compete” for the audience using the same content and the same strategies for it.